Application of thermographic measurements for the determination of the impact of selected cutting parameters on the temperature in the workpiece during milling process - Zgórniak, Piotr (Strojniški vestnik, 2016)
In this paper, the impact of selected cutting parameters (both cutting and feed speed) on the temperature generated in the workpiece being machined during milling is assessed. The investigations were carried out by milling of 41Cr4 alloy steel using disc cutter mill with F40M sintered carbide inserts with the anti-wear coating. The investigations were conducted with the dry cutting manner. During the investigations three cutting speeds and three feed speeds were applied, with a constant depth of cut. In the course of the investigations, the temperature in the machining, the zone was recorded using the Flir SC6000HS infrared camera. As a result of the measurements, the mean temperature in the defined measurement zone was determined, and, based on that, a procedure for the determination of the t sub W-max maximum temperature in the workpiece being machined has been proposed. Finally, on the basis of the obtained results, it has been found that the increase in cutting speed leads to the increase in the t sub W-max maximum temperature, whereas the increase in feed speed leads to the reduction of that temperature in the workpiece being machined.
Keywords: infrardeče meritve; IR-meritve; obdelava; rezkanje; temperatura obdelovanca; termografske meritve; toplotno slikanje